High-temperature impedance X7R dielectric ceramic material as well as preparation method and application thereof
Ceramic dielectric materials were prepared through the BaTiO3-Na0.5Bi0.5TiO3-Nb2O5-MeO-MgCO3 system to form core-shell structure and fine crystal structure, which solved the problem of high capacity change rate of ceramic dielectric materials under high temperature conditions, and achieved temperature stability and low dielectric loss.
Patent Information
- Application Number
- CN202411773243.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing ceramic dielectric materials have a high capacity change rate under high temperature conditions above 125°C, making it difficult to meet the high temperature stability requirements of military industry, aerospace and other industries.
The ceramic dielectric material was prepared by BaTiO3-Na0.5Bi0.5TiO3-Nb2O5-MeO-MgCO3 system. Through ball milling, prefiring and wet mixing, the core-shell structure and fine crystal structure were formed to improve the temperature characteristics of the dielectric ceramics.
The temperature stability of ceramic dielectric materials under high temperature conditions is achieved, and it complies with the X7R dielectric material standards formulated by the American Electronics Industry Association, and has good high-temperature impedance characteristics and low dielectric loss factor.
Smart Images

Figure CN119569447A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to a high-temperature impedance X7R dielectric ceramic material and a preparation method and application thereof. Background Art
[0002] At present, there are three main types of MLCC dielectric materials commonly used, lead-based composite perovskite system, tungsten bronze structure system, and BaTiO3 system. First, although the lead-based composite perovskite system has a low sintering temperature, it contains a large amount of lead, which will reduce reliability and cause great environmental harm. Secondly, although the tungsten bronze structure system has a high dielectric constant, the dielectric loss is also large and the high mobility of alkali metals also makes the MLCC dielectric properties unstable. In comparison, the BaTiO3 system has a strong spontaneous polarization effect and a high dielectric constant, making it the mainstream choice for high dielectric constant MLCC. However, since the Curie temperature of BaTiO3 is about 125°C, it is difficult to meet the TCC change rate requirement of ±15% under high temperature (>125°C) conditions. In special industries such as military industry, aerospace, etc., the upper limit of the operating temperature is generally above 150°C. Therefore, it is necessary to improve the dielectric temperature characteristics of BaTiO3 through doping modification, element control, process optimization and other measures to obtain stable capacitance dielectric temperature characteristics under wide temperature. Summary of the invention
[0003] In view of this, the purpose of the present invention is to propose a high temperature impedance X7R dielectric ceramic material and its preparation method and application, so as to solve the problem of high capacitance change rate of current ceramic dielectric materials under high temperature conditions above 125°C.
[0004] Based on the above purpose, the present invention provides a high temperature impedance X7R dielectric ceramic material, the raw materials of which include main powder, dopant, dispersant and binder, the main powder is composed of BaTiO3, Na 0.5 Bi 0.5 TiO3 is prepared by ball milling and pre-sintering at a molar ratio of 9:1, the pre-sintering temperature is 1200-1400°C, and the pre-sintering time is 2-4h; the dopant is obtained by pre-sintering Nb2O5, transition metal oxide MeO and MgCO3, the pre-sintering temperature is 650-750°C, and the pre-sintering time is 1-2h; in terms of molar parts, the main powder is 100 molar parts, the Nb2O5 is 0.1-1.0 molar parts, the MgCO3 is 0.1-1.0 molar parts, and the transition metal oxide MeO is 0.1-3.0 molar parts.
[0005] The BaTiO3 has a particle size of 150 to 500 nm and is prepared by a solid phase method. 0.5 Bi 0.5The amount of TiO3) accounts for 95-99 mol% of the total powder; the amount of dopants (Nb2O5, MeO, MgCO3) in the ceramic powder formula accounts for 0.3-5 mol% of the total powder.
[0006] BaTiO3 is used as the main phase to provide ferroelectric phase polarization performance, NBT is used as a peak shifter to move the Curie peak to the high temperature direction to meet the high temperature stability requirements, Nb elements are used as donor doping to promote the formation of core-shell structure, and MeO elements are used as acceptor doping to compensate for Nb 5+ Ion substitution Ti 4+ The charge imbalance caused by ions is adjusted to adjust the distribution of doping elements, and MgCO3 is used to inhibit grain growth and reduce dielectric loss.
[0007] A small amount of one or more submicron or nanometer transition metal element oxides and other additive components are added to the mixed powder composed of the main powder and the doping powder synthesized by the traditional solid phase method, and the mixture is wet mixed and dried to obtain the dielectric ceramic for MLCC. During the calcination process, some additives with low softening temperatures will preferentially dissolve into the liquid phase. As the temperature rises, the liquid phase increases, gradually wrapping the solid BaTiO3 grains that have not had time to grow, forming a shell-core structure, inhibiting the further growth of barium titanate grains, and finally dissolving fine-grained dielectric ceramics, improving the temperature characteristics of dielectric ceramics. Its temperature stability meets the X7R dielectric material standard established by the American Electronics Industry Association.
[0008] If the dopant does not include the aforementioned composition, the prepared dielectric ceramic material cannot meet the X7R standard and have good high temperature impedance characteristics and low dielectric loss factor.
[0009] In the transition metal oxide MeO, Me is any one or more of Fe, Ni, Co and Mn.
[0010] Based on 100 parts by weight of the mixed powder consisting of the main powder and the dopant, the added amount of the dispersant is 0.5 to 5 parts by weight, and the added amount of the binder is 5 to 15 parts by weight.
[0011] The dispersant includes polyethylene oxide resin. The dispersant is used to disperse the composition of the dielectric ceramic material. The dispersant of the present invention is not particularly limited, but in order to achieve the above-mentioned dispersion, the dispersant can be polyethylene oxide resin and other resins.
[0012] The adhesive includes polyvinyl acetal resin. The adhesive of the present invention is not particularly limited, but in order to achieve the above-mentioned bonding, the adhesive is polyvinyl acetal resin and other resins.
[0013] The method for preparing the high temperature impedance X7R dielectric ceramic material comprises the following steps:
[0014] S1, take the formula amount of BaTiO3 and Na 0.5 Bi 0.5 TiO3, mixed with ball mill at a molar percentage of 9:1, and pre-sintered into BT-NBT ceramic powder, namely the main powder; wherein the pre-sintering temperature is 1200-1400°C, and the pre-sintering time is 2-4h;
[0015] S2. Take the formulated amount of Nb2O5, MeO and MgCO3 and pre-sinter them at 650-750°C for 1-2h to synthesize the dopant;
[0016] S3, mixing the main powder obtained in S1 with the dopant obtained in S2, adding a dispersant and grinding to obtain a powder mixture;
[0017] S4, adding a binder and a solvent to the powder mixture to form a ceramic slurry after mixing;
[0018] S5, forming and drying the ceramic slurry to obtain a sheet;
[0019] S6. Sintering the sheet to obtain a high temperature impedance X7R dielectric ceramic material.
[0020] The powder mixture in S3 has a particle size D50 of 0.340-0.355 μm and a specific surface area of 3.5-3.6 m 2 / g.
[0021] The solvent in S4 includes one or more of water, anhydrous ethanol or toluene.
[0022] In the S6, the sintering temperature is 1230-1350° C., the sintering atmosphere is 0.5-3.5% H2-N2 by volume, and the sintering time is 4 hours.
[0023] The application of the high temperature impedance X7R dielectric ceramic material in multilayer ceramic capacitors.
[0024] The main reason why the dielectric properties of traditional BaTiO3-based dielectric materials decrease significantly above 125°C is that when the Curie temperature is higher than that, BaTiO3 undergoes a ferroelectric-paraelectric phase transition and its dielectric constant decreases significantly. Therefore, it is necessary to move the Curie temperature peak toward high temperature to meet the high temperature property requirements. 0.5 Bi 0.5 TiO3 has a high phase transition temperature (320°C) and has an ABO3 perovskite structure similar to BaTiO3, so it can form a solid solution with BaTiO3. 0.5 Bi 0.5The Na / Bi ions in TiO3 can jointly replace the Ba ions at the A position in BaTiO3 in a ratio of 1:1, which will affect the Ti-O bond binding energy in the adjacent Ti-O octahedron over a large area, causing the Curie temperature of BaTiO3 to move toward high temperature.
[0025] In order to make the dielectric system have good dielectric constant and temperature stability, it is necessary to form a core-shell structure in the grains. Nb is selected as the donor element to dope and replace the B-site Ti ions in BaTiO3. The addition of Nb causes the phase change peak (shell peak) in the high temperature zone of the dielectric material to be depressed and broadened, while the phase change peak (core peak) in the low temperature zone moves toward the low temperature direction. In addition, donor doping can also reduce oxygen vacancies and enhance the high temperature stability. Due to the superposition and leveling of the shell peak and the core peak, the temperature stability of the overall dielectric temperature curve is significantly improved.
[0026] MeO is used as an acceptor element for doping. MeO is a transition metal element added to (1-x)BaTiO3-xNa 0.5 Bi 0.5 When in the TiO3-Nb2O5 system, it will affect the reaction between the donor element Nb and BT, and then adjust the diffusion and distribution of Nb in the grains, that is, affect the core / shell ratio and relative strength in the grains, and improve the temperature stability of the system. In addition, acceptor doping can reduce dielectric loss, bind free-moving electrons, and enhance insulation resistance.
[0027] Due to the grain size effect, the grain size of BaTiO3 should not be too large. Therefore, in order to refine the grains and increase the dielectric constant, due to the consideration of Mg 2+ The diffusion rate of ions inside BaTiO3 grains is low, so Mg is used for B-site doping to form a paraelectric phase of Ba(Ti) outside the grains. x Mg 1-x )O3 thus encapsulates the pure phase BaTiO3. In addition, the denser shell layer will also inhibit the further diffusion of other doping elements inside the grains, which is conducive to the formation of a suitable microscopic core-shell structure.
[0028] Beneficial effects of the present invention:
[0029] The present invention adopts BaTiO3-Na 0.5 Bi 0.5Ceramic dielectric materials are prepared using the TiO3-Nb2O5-MeO-MgCO3 system. A small amount of two or more submicron or nanometer transition metal element oxides are added to the main powder, mixed evenly by wet method, dried, and then calcined to obtain dielectric ceramics for MLCC. During the calcination process of the dielectric ceramic, some additives with low softening temperatures will preferentially dissolve into liquid phase. As the temperature rises, the amount of liquid phase increases, gradually wrapping the solid BaTiO3 grains that have not had time to grow, forming a shell-core structure, inhibiting the further growth of barium titanate grains, and finally dissolving into fine-grained dielectric ceramics, thereby improving the temperature characteristics of the dielectric ceramics. The temperature stability meets the X7R dielectric material standard established by the American Electronics Industry Association.
[0030] When sintered in a reducing atmosphere, barium titanate easily loses oxygen at high temperature and becomes a semiconductor. Magnesium, calcium, manganese and other compounds act as acceptors during the calcination of the ceramic medium, causing oxygen vacancy concentrations greater than the oxygen vacancy concentrations formed by oxygen volatilization, so that barium titanate can maintain high electrical insulation resistivity when sintered in a reducing atmosphere. The invention complies with the X7R dielectric ceramic material formula and has good high-temperature impedance characteristics and low dielectric loss factor (tanδ). BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a flow chart for preparing the high temperature impedance X7R dielectric ceramic material of the present invention. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0034] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by people with ordinary skills in the field to which the present invention belongs. "Include" or "comprising" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, but do not exclude other elements or objects.
[0035] The relevant properties of the powder material used in the present invention are shown in Table 1:
[0036] Table 1: Selection of raw powder used
[0037] serial number Raw material name Particle morphology Particle size specification 1 <![CDATA[BaTiO3]]> Spherical or quasi-spherical 150-500nm 2 <![CDATA[Na 0.5 Bi 0.5 TiO3]]> Spherical or quasi-spherical 150-300nm 3 <![CDATA[Nb2O5]]> Spherical or quasi-spherical 30-40nm 4 <![CDATA[MgCO3]]> Spherical or quasi-spherical 30-50nm 5 MeO Spherical or quasi-spherical 30-60nm
[0038] The specific embodiments of the present invention are as follows:
[0039] Example 1
[0040] The preparation method of the high temperature impedance X7R dielectric ceramic material of this embodiment is carried out according to the following steps:
[0041] The main phase BaTiO3 and Na 0.5 Bi 0.5 TiO3 was mixed by solid phase method at a molar percentage of 9:1 (see Table 1 for material selection), and sintered at a sintering temperature of 1300°C for 3h to obtain the main powder; Nb2O5, MgCO3, MeO, etc. were mixed by solid phase method at a certain ratio (see Table 2 for material mixing ratio), and sintered at a sintering temperature of 700°C for 2h to obtain the dopant; 20% by mass percentage of toluene solvent, 20% by mass percentage of ethanol solvent and 1% by mass percentage of dispersant AKM-0531 were added to the mixed powder composed of the main powder and the dopant in a total of 100 parts by mass. After mixing evenly, the mixture was ground in a vertical bead mill for 3.5 hours, thereby obtaining a particle size D50 = 0.340 ~ 0.355um and a specific surface area BET = 3.5 ~ 3.6m 2 / g of slurry mixture, and then add 6% by weight of PVB (polyvinyl butyral resin) into the powder mixture, mix them evenly to obtain slurry, and then dry the slurry and press it into embryos.
[0042] Embodiment 2-6
[0043] Examples 2-6 were all manufactured in a similar manner to Example 1. The difference was that the amount of Nb2O5 was changed in Examples 2-6. The specific conditions and evaluation results are shown in Table 2 below.
[0044] Table 2: Main powder, dopant addition amounts and corresponding test results of Examples 1-6
[0045]
[0046] Referring to Table 2, it can be seen that the addition of the donor doping element Nb causes the dielectric material to form a core-shell structure. As the amount added increases, the proportion of the shell layer inside the grain decreases. The addition of Nb causes the phase change peak (shell peak) in the high temperature zone of the dielectric material to be depressed and broadened, while the phase change peak (core peak) in the low temperature zone moves toward the low temperature direction, which significantly increases its room temperature dielectric constant K value.
[0047] Preferably, when the doping amount of the donor element Nb2O5 is 0.2 mol%, the TCC of the dielectric material at -55°C to 125°C is no more than 15%, the dielectric constant K value reaches 2586, and the dielectric loss is less than 5%.
[0048] Examples 7-10
[0049] Examples 7-10 were all manufactured in a similar manner to Example 1. The difference was that the amount of Ni2O3 was changed in Examples 7-10. The specific conditions and evaluation results are shown in Table 3 below.
[0050] Table 3 Main powder, dopant addition amount and corresponding test results of Examples 7-10
[0051]
[0052] As shown in Table 3, when the acceptor element Ni2O3 is used for doping, it can make up for the donor element Nb 5+ In doping substitution Ti 4+ In order to avoid charge imbalance caused by the MgCO3, the donor-acceptor co-doping method is used to reduce oxygen vacancies and free electrons. In addition, the slow diffusion rate of MgCO3 can inhibit abnormal grain growth, adjust the core-shell ratio, and reduce dielectric loss.
[0053] Preferably, when the doping amount of the acceptor element Ni2O3 is 1.0 mol%, the TCC of the dielectric material at -55°C to 125°C is no more than 15%, the dielectric constant K value reaches 2586, and the dielectric loss is less than 5%.
[0054] Examples 11-14
[0055] Examples 11-14 were all manufactured in a similar manner to Example 1. The difference was that Examples 11-13 changed the element type of MeO, and Example 14 changed the amount of MgCO3 added. The specific conditions and evaluation results are shown in Table 4 below.
[0056] Table 4 Main powder, dopant addition amount and corresponding test results of Examples 11-14
[0057]
[0058] As shown in Table 4, when the acceptor element MeO is used for doping, the diffusion and distribution of Nb in the grains are adjusted, and the freely moving electrons are bound, and the core / shell ratio and relative strength in the grains are adjusted to reduce the dielectric loss. In addition, due to the slow diffusion rate of MgCO3, the abnormal growth of grains can be suppressed, the core-shell ratio can be adjusted, and the dielectric loss can be reduced.
[0059] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high temperature impedance X7R dielectric ceramic material, whose raw materials include main powder, dopant, dispersant and binder, characterized in that: The main powder is composed of BaTiO3, Na 0.5 Bi 0.5 TiO3 is prepared by ball milling and pre-sintering at a molar ratio of 9:1, the pre-sintering temperature is 1200-1400°C, and the pre-sintering time is 2-4h; the dopant is obtained by pre-sintering Nb2O5, transition metal oxide MeO and MgCO3, the pre-sintering temperature is 650-750°C, and the pre-sintering time is 1-2h; in terms of molar parts, the main powder is 100 molar parts, the Nb2O5 is 0.1-1.0 molar parts, the MgCO3 is 0.1-1.0 molar parts, and the transition metal oxide MeO is 0.1-3.0 molar parts.
2. The high temperature impedance X7R dielectric ceramic material according to claim 1, characterized in that: In the transition metal oxide MeO, Me is any one or more of Fe, Ni, Co and Mn.
3. The high temperature impedance X7R dielectric ceramic material according to claim 1, characterized in that: Based on 100 parts by weight of the mixed powder consisting of the main powder and the dopant, the added amount of the dispersant is 0.5 to 5 parts by weight, and the added amount of the binder is 5 to 15 parts by weight.
4. The high temperature impedance X7R dielectric ceramic material according to claim 1, characterized in that: The dispersant includes polyethylene oxide resin.
5. The high temperature impedance X7R dielectric ceramic material according to claim 1, characterized in that: The binder includes polyvinyl acetal resin.
6. The method for preparing the high temperature impedance X7R dielectric ceramic material according to any one of claims 1 to 5, characterized in that: The steps include: S1, take the formula amount of BaTiO3 and Na 0.5 Bi 0.5 TiO3, mixed with ball mill at a molar percentage of 9:1, and pre-sintered into BT-NBT ceramic powder, namely the main powder; wherein the pre-sintering temperature is 1200-1400°C, and the pre-sintering time is 2-4h; S2. Take the formulated amount of Nb2O5, MeO and MgCO3 and pre-sinter them at 650-750°C for 1-2h to synthesize the dopant; S3, mixing the main powder obtained in S1 with the dopant obtained in S2, adding a dispersant and grinding to obtain a powder mixture; S4, adding a binder and a solvent to the powder mixture to form a ceramic slurry after mixing; S5, forming and drying the ceramic slurry to obtain a sheet; S6. Sintering the sheet to obtain a high temperature impedance X7R dielectric ceramic material.
7. The method for preparing the high temperature impedance X7R dielectric ceramic material according to claim 6, characterized in that: The powder mixture in S3 has a particle size D50 of 0.340-0.355 μm and a specific surface area of 3.5-3.6 m 2 / g.
8. The method for preparing the high temperature impedance X7R dielectric ceramic material according to claim 6, characterized in that: The solvent in S4 includes one or more of water, anhydrous ethanol or toluene.
9. The method for preparing the high temperature impedance X7R dielectric ceramic material according to claim 6, characterized in that: In the S6, the sintering temperature is 1230-1350° C., the sintering atmosphere is 0.5-3.5% H2-N2 by volume, and the sintering time is 4 hours.
10. Use of the high temperature impedance X7R dielectric ceramic material according to any one of claims 1 to 5 in a multilayer ceramic capacitor.
Citation Information
Patent Citations
High performance multilayer ceramic capacitor medium and preparation method thereof
CN102363579A
High-dielectric-constant X8R type dielectric material for multilayer porcelain capacitor, and preparation method for dielectric material
CN105036734A
Temperature-stable X8R MLCC (multiplayer ceramic chip capacitor) medium material with low-temperature sintering effect
CN108083795A
Wide-temperature-spectrum ceramic capacitor dielectric material and preparation method thereof
CN114804856A
Reduction-resistant dielectric composition, and ceramic electronic component containing the same
JP2012036080A
Cited By
BaTiO3-based high dielectric ceramic with positive temperature coefficient at low temperature
CN121850641A